The Fragile X Protein binds mRNAs involved in cancer progression and modulates metastasis formation. Issue 10 (16th September 2013) - Lucá, Rossella; Averna, Michele; Zalfa, Francesca; Vecchi, Manuela; Bianchi, Fabrizio; Fata, Giorgio La; Del Nonno, Franca; Nardacci, Roberta; Bianchi, Marco; Nuciforo, Paolo; Munck, Sebastian; Parrella, Paola; et al.
<x xml:space="preserve">Abstract</x> The role of the fragile X mental retardation protein (FMRP) is well established in brain, where its absence leads to the fragile X syndrome (FXS). FMRP is almost ubiquitously expressed, suggesting that, in addition to its effects in brain, it may have fundamental roles in other organs. There is evidence that FMRP expression can be linked to cancer. FMR1 mRNA, encoding FMRP, is overexpressed in hepatocellular carcinoma cells. A decreased risk of cancer has been reported in patients with FXS while a patient‐case with FXS showed an unusual decrease of tumour brain invasiveness. However, a role for FMRP in regulating cancer biology, if any, remains unknown. We show here that FMRP and FMR1 mRNA levels correlate with prognostic indicators of aggressive breast cancer, lung metastases probability and triple negative breast cancer (TNBC). We establish that FMRP overexpression in murine breast primary tumours enhances lung metastasis while its reduction has the opposite effect regulating cell spreading and invasion. FMRP binds mRNAs involved in epithelial mesenchymal transition (EMT) and invasion including E‐cadherin and Vimentin mRNAs, hallmarks of EMT and cancer progression.